Unstoppable us. Vol. 1, How humans took over the world - Harari, Yuval N. (Bright Matter Books, 2022)
This illustrated book for middle-grade readers looks at the early history of humankind. Even though we'll never outrun a hungry lion or outswim an angry shark, humans are pretty impressive -- and we're the most dominant species on the planet. So how exactly did we become "unstoppable"? From learning to make fire and using the stars as guides to cooking meals in microwaves and landing on the moon, prepare to uncover the secrets and superpowers of how we evolved from our first appearances millions of years ago.